Picturing mind : paradox, indeterminacy and consciousness in art & poetry - Danvers, John. (Amsterdam ; New York : Rodopi, 2006)
In this book the author takes an unusual multi-disciplinary approach to debates about contemporary art and poetry, ideas about the mind and its representations, and theories of knowledge and being. Arts practices are considered as enactments of mind and as transformative modes of consciousness. Ideas drawn from poetics, philosophy and consciousness studies are used to illuminate the conceptual and aesthetic frameworks of a diverse array of visual artists. Themes explored include: the interconnectedness of existence; art as a way of interrogating appearances; identity and otherness; art and the.
Preface; Part 1: Introduction -- an opening, an entering; Part 2: The knowing body: art as an integrative process of cognition; Part 3: Interrogating appearances: being, seeing & showing; Part 4: The mutuality of existence: drawing, emptiness & presence; Part 5: Picturing mind -- writing being; Part 6: The self as open-work: permeability, incompleteness & revisibility; Part 7: Mind, the real & the other; Part 8: Where we are: locus of mind-in-the-world; Part 9: The! the One & the Many: mysticism, art & poetry.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Literature -- Philosophy; Art -- Philosophy; Philosophy of mind; Knowledge, Theory of; Consciousness; Consciousness; Art -- Philosophie; Philosophie de l'esprit.; Théorie de la connaissance; Conscience; epistemology; LITERARY CRITICISM -- Semiotics & Theory; Art -- Philosophy; Consciousness; Knowledge, Theory of; Literature -- Philosophy; Philosophy of mind; Electronic book